2012
DOI: 10.3109/0142159x.2012.733454
|View full text |Cite
|
Sign up to set email alerts
|

Mobile learning in resource-constrained environments: A case study of medical education

Abstract: Background: The achievement of the millennium development goals may be facilitated by the use of information and communication technology in medical and health education. Aims: This study intended to explore the use and impact of educational technology in medical education in resource-constrained environments. Methods: A multiple case study was conducted in two Nepalese teaching hospitals. The data were analysed using activity theory as an analytical basis. Results: There was little evidence for formal e-learn… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
45
0
4

Year Published

2014
2014
2020
2020

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 56 publications
(56 citation statements)
references
References 43 publications
5
45
0
4
Order By: Relevance
“…In this sense, mobile phones, and in particular the convergence of mobile and social media, can support learners in alleviating professional isolation, as it was also indicated in the literature (Morley, 2013;Young et al, 2010). These findings are also in line with other studies from low resource settings showing how mobile phones support socio-cultural participation and identity formation (Pimmer et al, 2012(Pimmer et al, , 2013a and enhance professional relationships (Chib, 2010).…”
Section: Rich Mobile Learning Practicessupporting
confidence: 83%
See 1 more Smart Citation
“…In this sense, mobile phones, and in particular the convergence of mobile and social media, can support learners in alleviating professional isolation, as it was also indicated in the literature (Morley, 2013;Young et al, 2010). These findings are also in line with other studies from low resource settings showing how mobile phones support socio-cultural participation and identity formation (Pimmer et al, 2012(Pimmer et al, , 2013a and enhance professional relationships (Chib, 2010).…”
Section: Rich Mobile Learning Practicessupporting
confidence: 83%
“…By contrast, nurses used mobile phones to organize and support learning to better address unforeseen and unpredictable occurrences, characteristics that are typical of clinical settings in general (Pimmer et al, 2013b) and particularly in the changing macro-and socioeconomic health contexts in South Africa (Coovadia et al, 2009). In addition, nurses used mobile phones to connect situated experiences with sources and communities, even across phases of their career trajectories in the sense of life-long learning (Pimmer et al, 2013a).…”
Section: The Changed Meaning Of Learning Environmentsmentioning
confidence: 99%
“…Several studies have indicated that mobile, wireless device technology supports teaching and learning [6,7]. An increasing number of physicians, residents, and medical students currently use mobile devices such as Smartphones, iPads, and Tablets for education and use in clinical environments [8,9]. Medical students have to assimilate considerable new information during their studies especially with the need for evidence-based practice, and they must develop skills for lifelong learning, keeping their knowledge updated [10].…”
Section: Introductionmentioning
confidence: 99%
“…[5,6] An increasing number of physicians, residents, and medical students currently use mobile devices such as Smartphones, iPads, and Tablets for education and use in clinical environments. [7,8] Medical students need to assimilate considerable new information during their studies especially with the need for evidence-based practice, and they must develop skills for lifelong learning, keeping their knowledge updated. [9] Lifelong learning, particularly in medicine, requires motivation and problem identification and solving skills relevant to the clinical situation.…”
Section: Introductionmentioning
confidence: 99%